Assessment of soil resources of Pauri Garhwal district of Uttarakhand for sustainable productivity - NAGDEV, RITU; MAHAPATRA, S. K. (Journal of Soil and Water Conservation, 2020)
A study was undertaken to assess the soil resources of Pauri Garhwal district of Uttarakhand using remote sensing and GIS techniques. The area falls under warm humid lesser western Himalayas, covering 5.33 lakh ha area. Major physiographies are summits/ridge tops, side/reposed slopes, piedmont plains and escarpments with dominant land uses viz., forests (thin, medium and dense), scrubs, cultivations and grasslands. Twenty five soil series have been identified belonging to Entisols, Inceptisols and Mollisols. The study reveals that the area occurs mostly on steep to very steep slopes and prone to severe to very severe soil erosion. The soil is dominantly moderately shallow (29.54%) followed by shallow (22.7%), very shallow (15.59%), deep (12.78%), moderately deep (11.62%) and very deep (7.77%), respectively. The texture is dominantly loam (35.33%), followed by sandy loam (27.10%), clay loam (26.44%) and loamy sand (11.13%), respectively. The stoniness is mostly strong (67.19%) followed by slight (21.92%) and moderate (10.89%), whereas, soil reaction is dominantly slightly acidic (66.06%) followed by neutral (23.55%) and moderately acidic (10.39%), respectively. The land has been categorised under land capability classification (LCC) and major soils belong to class VIes (39.02%), followed by IIIes (17.98%), VIIIes (15.98%), Vse (7.55%), VIIes (6.77%), IVes (6.23%), IIIse (4.45%) and IIes (2.02%), respectively. The suitable soil and water conservation measures have been suggested to arrest soil erosion, proper soil management and to maintain soil health towards ensuring sustainable productivity of this hilly region